WALDO AS THE MEDIA TO TEACH ENGLISH TENSES - Andi Dian Rahmawan (Journal of English Language Teaching and English Linguistics, 2016)
In language teaching learning, teaching takes place as the primary activity. However, information about people’s language ability can be acknowledged from a useful and necessary testing. This useful device is highly considered because having the knowledge of a language, which is one’s linguistic competence is different to using this knowledge in actual production, which is one’s linguistic performance. A test as a subset of assessment, in simple terms, is a method of measuring a person’s ability, knowledge, or performance in given domain (Brown, 2004:3). Component of keywords related to this definition can be seen as (1) method – a set of techniques, procedures, or items that requires performance of the test-taker, (2) measure – to measure general ability, (3) individual’s ability, competence and performance – to understand who the test-takers are and (4) domain – a sample that represents general competence.